Cultural geographies an introduction - Horton, John 1977-; Kraftl, Peter (Routledge, 2014)
"Description Cultural geography is a major, vibrant subdiscipline of human geography. Cultural geographers have done some of the most important, exciting and thought-provokingly zesty work in human geography over the last half-century. This book exists to provide an introduction to the remarkably diverse, controversial, and sometimes-infuriating work of cultural geographers. The book outlines how cultural geography in its various forms provides a rich body of research about cultural practices and politics in diverse contexts. Cultural geography offers a major resource for exploring the importance of cultural materials, media, texts and representations in particular contexts and is one of the most theoretically adventurous subdisciplines within human geography, engaging with many important lines of social and cultural theory. The book has been designed to provide an accessible, wide-ranging and thought-provoking introduction for students studying cultural geography, or specific topics within this subdiscipline. Through a wide range of case studies and learning activities, it provides an engaging introduction to cultural geography"--Provided by publisher.